Provider Initiated Testing and Counseling (PITC) Strategy Increased Coverage of HIV detection among TB Patients : English Language - sity kunarisasi; Febianza Mawaddah Putri; Sarah At Tauhidah (Journal of Health Science and Prevention, 2022)
Indonesia is one of the six countries with a high burden of TB and HIV. The prevalence of TB-HIV cases at all ages is as much as 4.9%; The study aimed to provide an assessment of PITC implementation in high coverage and low coverage in HIV detection among TB patients. This study descriptive, analytic, cross-sectional with the consecutive sampling method. Data used in this research was secondary data collected from January until December 2017 conducted in 5 of the 23 cities with a high burden of TB-HIV. Using a routine reporting system by primary health care and regional health service in the district. The total sample size included TB patients registered in 5 cities 16.097 patients, 8022 patients (2.365 from low PITC, 5657 from high PITC) TB patients who had received the PITC program of this 3,5% were HIV positive. Additionally, was detected by percentage among TB patients in the high-coverage PITC area compared to in the low-coverage PITC area was 4.3:2.6. Male patients had a double risk of having HIV-positive results compared to female patients. Furthermore, the analysis also showed that productive age patients are more likely to have HIV infection compared to other age groups. Male sex aged 26 to 36 years 78-94% of them were at risk of having HIV infection. The implementation of PITC in countries with high TB ​​/ HIV burden has shown an increase in TB-HIV patient detection but still needs to be followed by ARV treatment to reduce mortality.